Biosynthesis of Gold Nanoparticles Mediated by Andaliman Fruit Water Extract and Its Application as Antioxidants - Gusti Ayu Dewi Lestari; Kadek Duwi Cahyadi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Plant extract-mediated green synthesis of gold nanoparticles (AuNPs) is currently gaining significant interest in the field of nanotechnology. In this study, AuNPs were synthesized using an aqueous extract of Andaliman fruit (Zanthoxylum acanthopodium DC.). The formation of AuNPs was confirmed by observing the color change of the solution from clear to cherry red. The reaction parameters, namely the extract concentration and the ratio of the mixture of the extract with HAuCl4 solution, were optimized for the AuNPs biosynthesis. The gold nanoparticles were characterized using a UV-Vis spectrophotometer, SEM-EDS, and particle size analyzer. The characterization suggested that AuNPs had a maximum wavelength ranging of 540–559 nm, with spherical crystals morphology where the highest component was gold at 36.01% and the size below 100 nm on average. The antioxidant activity of the synthesized AuNPs was determined using the DPPH method. It showed that the highest free radical scavenging activity was 83%, given by 20 ppm AuNPs.